Prediction Of Critical Values For Onset Of Convection By Vertical Heated Plate In Water Under Constant Heat Flux Condition - Ngeow, Yen Wan (2007)

(untitled)
The local onset of convection in water generated by vertical heated plate is examined. It is generally accepted that the occurrence of buoyancy convection can be predicted using well known conventional critical Rayleigh number derived by Lord Rayleigh (1916). However, the development of local transient instability is less well understood for fluids suddenly heated by vertical heating plate. In this work, the correlation between local onset of convection and distance from the leading-edge has been derived and has allowed the tracking of local critical time along the heating plate. Patterson et al. (2002) experiments have been reproduced based on Constant Heat Flux (CHF) boundary condition. Experiments of Patterson et al. (2002) have shown that the local onset of convection occurred at the departure from the initial heat conduction temperature profile. The characteristic of temperature profile along the vertical heated plate for x-axis and y-axis have been studied to determine the correlation between the local onset of convection and the distance from the leading-edge along the heating plate. Subsequently, simulations under different vertical heated plate lengths and heat fluxes have been simulated to study the effect for both of these conditions. A computational fluid dynamics (CFD) software, Fluent 6.0 is used in this study to solve the governing partial differential equations for heat transfer using finite volume technique under various heat fluxes and plate lengths. 2D-time simulations were conducted for constant heat flux (CHF) boundary conditions. Various heat fluxes and plate lengths were applied and the effects were investigated. The mechanism of the local onset of convection by the vertical heating plate was observed. The temperature profiles, velocity magnitude and heat transfer coefficient versus time were plotted to detect the local onset of convection. The newly derived correlation of local onset of convection was incorporated in this study to predict the local critical time and compare with the simulated results. It is observed that the local critical Rayleigh number is consistent with respect to their location and is independent of heating plate length. The local critical time is earlier as the heat flux is increased under the same heating plate length.Approximately 280 simulations were conducted and most of these simulated local critical Rayleigh number were in good agreement with the predicted value using the newly derived equation.